Investigation of oxygen evolution reaction with Ni foam and stainless-steel mesh electrodes in alkaline seawater electrolysis. Issue 5 (October 2022) - Lyu, Xiang; Li, Jianlin; Jafta, Charl J.; Bai, Yaocai; Canales, Camila P.; Magnus, Fridrik; Ingason, Árni S.; Serov, Alexey
Abstract: Alkaline seawater electrolysis is a promising method for hydrogen production; however, little progress has been made in investigating the substrates for oxygen evolution reaction (OER) electrocatalysts. Ni foam and stainless-steel mesh (SS mesh) were investigated systematically for OER in alkaline seawater electrolysis in this work. The overpotentials and Tafel slopes with SS meshes are smaller than Ni foams, and it also exhibits excellent stability. Interestingly, the performance of the SS mesh even outperforms various non-noble metal electrocatalysts and is comparable to commercial RuO2 and IrO2 . The corrosion conditions of Ni foam and SS mesh electrodes were studied and revealed. Furthermore, the electrochemically active surface area (ECSA) of Ni foam is 12 times higher than SS mesh in the same geometric area, indicating the electrochemical activity of SS mesh is much superior to Ni foam. This work expands on promising substrates for alkaline seawater electrolysis, with cost and performance advantages. Highlights: Ni foam and stainless-steel meshes were systematically evaluated for seawater electrolysis. The SS mesh is superior to Ni foam based on potential, Tafel slope, and stability. The performance of SS mesh outperforms various non-noble metal catalysts. The performance of SS mesh is comparable to commercial RuO2 and IrO2 catalysts. The corrosion conditions of Ni form and SS mesh were revealed and investigated.